A Meta‐Analysis of Friendship Qualities and Romantic Relationship Outcomes in Adolescence. (17th May 2019) - Kochendorfer, Logan B.; Kerns, Kathryn A.
Abstract : Romantic relationships are one of the most significant interpersonal ties in adolescence, thus understanding factors that may contribute to their formation and quality are important. The current meta‐analysis focuses on links between friendship quality and romantic relationship outcomes for adolescents up to 18 years. In a series of meta‐analyses ( k = 28 studies, N 's = 946–4, 040), friendship qualities were not related to romantic involvement. However, we did find robust evidence of continuity between friendship qualities and romantic relationship qualities. Additionally, adolescents experienced more negative quality in their romantic relationships than in their friendships. These findings suggest that friendships have implications for adolescents' romantic relationships, although more research is needed on specific quality associations, and the mediators of these relations.